Salt marsh erosion in a microtidal estuary. Issue 2 (3rd April 2021) - Riddin, T; Adams, JB
Abstract : Salt marshes protect estuary banks from erosion by acting as buffers between marine and terrestrial environments. Residents living near the Breede River estuary, Western Cape Province, South Africa, raised concerns about ongoing erosion evident at Groenpunt, the main salt marsh. This study aimed to determine how long erosion has been taking place, the rate and possible causes thereof. Aerial images and environmental data were assessed for the years 2002–2020. Erosion was first evident in 2003. By 2020, the marsh edge had been eroded into a series of micro-bays, incised horizontally up to 7 m, with a scarp height of 0.7 m, corresponding to a loss of 1 313 m 2 of salt marsh and a bank retreat rate of 0.66 (SE 0.44) m year −1 . Over the study period, there was a regular pattern of high-frequency gale-force winds (>8 on the Beaufort scale), with significantly more winds of this magnitude occurring in 2002 than in other years. The wind wave fetch adjacent to the marsh is up to 1 km in the direction of the predominant wind, and it is likely that the cumulative effects of constant wind-generated waves drove the erosion process. Estuary water and tidal levels over the period reflected normal seasonal fluctuation patterns. The bank supporting Groenpunt salt marsh is eroding at a rate that could possibly see it disappear within the next 60 years, reducing biodiversity and ecosystem services in the estuary. In the face of increasing climatic variability predicted in the future, similar salt marsh erosion is likely to become more prevalent.